It whispered in the wind, it lingered on my skin - Lee, Noah Yong Ler (Nanyang Technological University, 2023)
In exploring how suicidal ideation exists as a spectrum, It Whispers in the Wind, It Lingers on the Skin (2023) reflects upon my own experience of living with long-term Passive Suicidal Ideation (PSI). Manifesting as feelings such as lacking a will to live, dreading the fact of existence, or desperately wishing for non-existence, it is something that I am seeing people my age identify with more and more but struggle to talk about or have the mental space to hold for one another. The work leans into the ubiquitous experience of weightedness and the clinging grasp of water as metaphors of living with such low mood states, to reach out in assurance to others who have or might feel similarly, that we are not alone in our not-so-ok brains.